Time Series Analysis of Daily Bed Costs and Consumption Ratio of Inpatients with CHD in a Children’s Hospital in Chengdu - Yang H; Xiang S; Yang Y (Risk Management and Healthcare Policy)
Honglin Yang, Siyu Xiang, Yuwei Yang West China Second University Hospital, Sichuan University, Office of Operations Management and Evaluation, Chengdu, Sichuan, 610000, People’s Republic of ChinaCorrespondence: Yuwei Yang, Email canbiezan555@163.comObjective: This study aims to examine the evolving trends in daily bed costs and the ratios of consumables costs for inpatients with congenital heart disease (CHD) at a pediatric hospital in Chengdu from 2019 to 2024 and to project these metrics for the year 2025.Methods: Utilizing SPSS version 23.0, we employed exponential smoothing and ARIMA models to analyze the daily bed cost data of CHD inpatients from 2019 to 2023, constructing predictive models accordingly. The annual data for 2024 were forecasted and subsequently compared with actual values to assess model accuracy. Visualization of Mean Absolute Percentage Error (MAPE) charts was conducted to identify the optimal model, which was then utilized to predict daily bed costs and consumables cost ratios for 2025.Results: Between 2019 and 2023, both daily bed costs and consumables cost ratios for CHD patients exhibited a consistent annual increase. A decline was noted in 2024, with projections for 2025 suggesting increases to approximately 5,600 CNY and 47%, respectively.Conclusion: For operational recommendations, it is advised that the hospital prioritizes the management of high-value consumables in CHD care and considers piloting disease-specific cost accounting within cardiovascular departments. From a policy perspective, there is an urgent need to optimize China’s existing medical insurance payment system for pediatric hospitals to address the rising healthcare costs.Keywords: congenital heart disease, daily bed costs, time series analysis, MAPE